2010
DOI: 10.1111/j.1528-1167.2010.02740.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of epilepsy in Kolkata, India

Abstract: SUMMARYPurpose: This study aimed to determine the prevalence, incidence, and mortality rates of epilepsy in the city of Kolkata, India. This is the first such longitudinal study in a heterogeneous urban Indian population. Methods: A two-stage door-to-door survey of a stratified random sample was undertaken within the municipal limits of Kolkata. Trained field workers detected and interviewed the cases using a simple screening questionnaire, and the detailed follow-up was done by neurologists. The survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 24 publications
3
82
3
Order By: Relevance
“…Some studies report significantly higher prevalence rates in the developing countries as compared to developed countries 12.7/1,000 in rural areas and 5.9/1,000 in urban areas [3, 4]. From 1964 onwards, various epidemiology studies in India have reported widely varying prevalence rates ranging between 1.3 and 11.9 per 1,000 population [5-11]. The application of epidemiological data of epilepsy extends beyond prevalence and incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report significantly higher prevalence rates in the developing countries as compared to developed countries 12.7/1,000 in rural areas and 5.9/1,000 in urban areas [3, 4]. From 1964 onwards, various epidemiology studies in India have reported widely varying prevalence rates ranging between 1.3 and 11.9 per 1,000 population [5-11]. The application of epidemiological data of epilepsy extends beyond prevalence and incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Though recently conducted study in Calcutta has some similar incidence profile comparable to this study. 11 Study population of 66. Incidence of myoclonic epilepsy in Hodskins et al was found to be 10 to 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Hence an early diagnosis of this condition is important to counsel them regarding certain benign conditions, to start specific treatment to attain remission and for giving advice regarding the prognosis to the parents. There are several Indian studies in the past which shows the prevalence of epilepsy to be were 572.8 (509.79-641.54) per 100, 000 (2) . Another study by Shah PA et al found the age-specific prevalence was3.82/1000 (6-10 years), 3.44/1000 (11-14 years) and 2.33/1000 (15-18 years) (3) .Prevalence studies from India suggest that epilepsy prevalence is similar to developed nations (4) .There are limited studies in children in this part of our country to find the varying clinical pattern of epilepsy.…”
Section: Introductionmentioning
confidence: 99%